Directional Coupler: Impact of the Energetic Landscape on Polariton Condensates' Propagation along a Coupler (Advanced Optical Materials 18/2020). Issue 18 (21st September 2020) - Rozas, Elena; Beierlein, Johannes; Yulin, Alexey; Klaas, Martin; Suchomel, Holger; Egorov, Oleg; Shelykh, Ivan Andreevich; Peschel, Ulf; Schneider, Christian; Klembt, Sebastian; Höfling, Sven; Martín, María Dolores; et al.
Abstract : Semiconductor microcavities offer extraordinary opportunities for the control and manipulation of light. A plethora of devices ranging from polariton lasers to integrated circuits have been proposed in the last decade. In article number 2000650, Maria Dolores Martin and co‐workers provide essential information about the energy landscape and the impact of the geometry on the polariton condensates' propagation along a novel device, a directional coupler.